1991
DOI: 10.1017/s0305000900013283
|View full text |Cite
|
Sign up to set email alerts
|

Directive interactions and early vocabulary development: the role of joint attentional focus

Abstract: Maternal directiveness, assessed by the mother's use of prescriptives, is correlated with slow vocabulary development. As prescriptives are most often used to redirect a child's attention to a different object or activity, it is hypothesized that attentional regulation underlies this negative relationship. In the present study, twelve mothers were videotaped interacting with their children aged 1;1, and 100 maternal utterances were coded for pragmatic intent. Prescriptives were coded as either changing (LEADIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
263
3
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(298 citation statements)
references
References 20 publications
18
263
3
11
Order By: Relevance
“…Previous work on the impact of parental directiveness on child language development has had mixed findings (Akhtar et al, 1991;Barnes et al, 1983;Hampson & Nelson, 1993;Tomasello & Farrar, 1986). This study found positive associations between father directive behavior and later father vocabulary, which may be explained by several factors.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Previous work on the impact of parental directiveness on child language development has had mixed findings (Akhtar et al, 1991;Barnes et al, 1983;Hampson & Nelson, 1993;Tomasello & Farrar, 1986). This study found positive associations between father directive behavior and later father vocabulary, which may be explained by several factors.…”
Section: Discussionsupporting
confidence: 40%
“…Such contradictory findings may speak to the fact that parents may use directives in interactions with their children in different ways that may be supportive or intrusive. Akhtar et al (1991) found that maternal directives that followed children's attentional focus were positively associated with children's later vocabulary development, while maternal directives that redirected children's attention negatively predicted later vocabulary development. Similarly, Masur et al (2005) found that during the second year of life, maternal supportive directiveness, which attempted to follow and extend the child's current activity, was positively associated with child vocabulary, while more intrusive directiveness was negatively associated with child vocabulary.…”
Section: Parent-child Interactionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our findings provide support and also greater specificity to previous findings. Contrary to some earlier studies that examined only productive vocabulary as an outcome measure (Akhtar et al, 1991;Bornstein et al, 1999;Masur et al, 2005), in the present study also receptive skills were assessed. Furthermore, the present study was carried out in a new language community (Finnish).…”
Section: Discussionmentioning
confidence: 92%
“…Snow (1995) on esittänyt, että lapselle suunnatun puheen sisällön sovittaminen lapsen sen hetkiseen kielelliseen tasoon ei riitä tukemaan pienen lapsen kehitystä, mikäli puhe on hyvin ohjailevaa ja pyrkii jatkuvasti suuntaamaan lapsen huomion uusiin kohteisiin. Itse asiassa jatkuvilla lapsen huomiota uudelleen suuntaavilla ilmauksilla on todettu olevan yhteyttä hitaampaan varhaisen sanaston kehitykseen (Akhtar, Dunham & Dunham, 1991;Della Corte, Benedict & Klein, 1983;Masur ym., 2005). Sen sijaan responsiivisuuden eli kyvyn vastata lapsen aloitteisiin nopeasti, johdonmukaisesti ja tarkoituksenmukaisesti lapsen aikomuksia ja tunteita oikein tulkiten on usean tutkimuksen mukaan todettu tukevan sanaston kehitystä (Bornstein ym., 1999;Girolametto ym., 1999Girolametto ym., , 2002Hoff & Naigles, 2002;Kaiser & Hancock, 2003;Masur ym., 2005;Paavola, 2006;Roberts & Kaiser, 2011).…”
unclassified